PENGARUH MEDIA BUSY BOOK TERHADAP KEMAMPUAN MOTORIK HALUS ANAK USIA 5-6 TAHUN DI TK ALFALAH NAUMBAI KECAMATAN KAMPAR KABUPATEN KAMPAR - Hasnita Hasnita; Daviq Chairilsyah; Enda Puspitasari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract. This study aims to determine the effect of the busy book media on the fine motor skills of children aged 5-6 years in Alfalah Naumbai Kindergarten, Kampar District, Kampar Regency. This research was conducted at Alfalah Naumbai Kindergarten, Kampar District, Kampar Regency and aimed at parents and teachers. The research is conducted after the seminar proposal, namely in August 2018.This study uses an experimental method that is research to determine the relationship between two variables by measuring coefficient or significant by using statistics with independent variables (x), namely busy book media and Dependent (y) variables, namely fine motor skills. To determine the sample of the study, researchers used a saturated sample technique that is taking the entire population into a sample. This means that the sample was taken from only 1 class, then the sample in this study were 20 children in class A children.Based on the formulation of the problem, it can be concluded that the effect of the busy book media on the fine motor skills of children aged 5-6 years in Alfalah Naumbai Kindergarten, Kampar District, Kampar Regency is 74.81%. Where in the gain category normalized in the medium category. That is, the influence of the busy book media on the fine motor skills of children aged 5-6 is. This means that there is a significant effect with the busy book media on the fine motor skills of children aged 5-6 years in Alfalah Naumbai Kindergarten, Kampar District, Kampar Regency.Keywords: Busy Book, Fine Motor.